DelPhiPKa web server: predicting pK(a) of proteins, RNAs and DNAs - Wang, Lin (Bioinformatics, 2016)
Summary: A new pK(a) prediction web server is released, which implements DelPhi Gaussian dielectric function to calculate electrostatic potentials generated by charges of biomolecules. Topology parameters are extended to include atomic information of nucleotides of RNA and DNA, which extends the capability of pK(a) calculations beyond proteins. The web server allows the end-user to protonate the biomolecule at particular pH based on calculated pK(a) values and provides the downloadable file in PQR format. Several tests are performed to benchmark the accuracy and speed of the protocol. Implementation: The web server follows a client-server architecture built on PHP and HTML and utilizes DelPhiPKa program. The computation is performed on the Palmetto supercomputer cluster and results/download links are given back to the end-user via http protocol. The web server takes advantage of MPI parallel implementation in DelPhiPKa and can run a single job on up to 24 CPUs. Availability and implementation: The DelPhiPKa web server is available at http://compbio.clemson.edu/pka_webserver. Contact: lwang3@clemson.edu or ealexov@clemson.edu Supplementary information: Supplementary data are available at Bioinformatics online.